CROSSROADS—Organizing for Fluidity? Dilemmas of New Organizational Forms - Schreyögg, Georg; Sydow, Jörg (Organization Science, 2010)
An important new stream of thought stressing the importance of organizational fluidity has emerged in recent years. It represents a reaction to the increasing complexity and environmental turbulence that organizations have to master. The solutions proposed are highly flexible and fluid organizational forms, based on relentlessly changing templates, quick improvisation, and ad hoc responses. This approach is in sharp contrast to other recent organizational research that emphasizes identity, path dependence, economies of specialization, and recursive practices. We juxtapose the idea of organizational fluidity with this latter stream of research. If taken to its final conclusion, then the idea of promoting organizational fluidity would imply losing the very essence of organizing. Nevertheless, achieving organizational flexibility remains imperative in increasingly complex and volatile environments. To deal with this dilemma, an alternative approach is needed. We suggest a conceptualization of this dilemma that emphasizes the complementary dynamics between the two perspectives. We therefore provide an alternative conception that favors the idea of balancing countervailing processes in organizations with respect to the conflicting demands of organizational efficiency and fluidity.